Niche appropriation by Drosophila intestinal stem cell tumours - Patel, Parthive H.; Dutta, Devanjali; Edgar, Bruce (Nature cell biology, 2015)
Mutations that inhibit differentiation in stem cell lineages are a common early step in cancer development, but precisely how a loss of differentiation initiates tumorigenesis is unclear. We investigated Drosophila intestinal stem cell (ISC) tumours generated by suppressing Notch (N) signalling, which blocks differentiation. Notch-defective ISCs require stress-induced divisions for tumour initiation and an autocrine EGFR ligand, Spitz, during early tumour growth. On achieving a critical mass these tumours displace surrounding enterocytes, competing with them for basement membrane space and causing their detachment, extrusion and apoptosis. This loss of epithelial integrity induces JNK and Yki/YAP activity in enterocytes and, consequently, their expression of stress-dependent cytokines (Upd2, Upd3). These paracrine signals, normally used within the stem cell niche to trigger regeneration, propel tumour growth without the need for secondary mutations in growth signalling pathways. The appropriation of niche signalling by differentiation-defective stem cells may be a common mechanism of early tumorigenesis.